The Characteristics of Cytochrome C Oxidase Gene Subunit I in Wild Silkmoth Cricula trifenestrata Helfer and Its Evaluation for Species Marker - . Suriana; D D Solihin; R R Noor; A M Thohari (Faculty of Animal Science, Bogor Agricultural University, 2012)
The study was conducted to assess the characteristics of partial gene of cytochrome C oxidase subunit I (COI) of wild silkmoth Cricula trifenestrata, and to detect the diagnostic sites from these gene for evaluation as species marker. A total of fifteen larvae of C. tifenestrata were collected from Bogor, Purwakarta, and Bantul Regencies. Genomic DNA was extracted from silk gland of individual larvae, then amplified by PCR method and sequenced. DNA sequencing was done to characterize their nucleotide and amino acid contents. The results showed that 595 nucleotides at the 5 'end of COI gene of C. tifenestrata was conserved at the species level, but varies at the family level. Nucleotide dominated by thymine and adenine bases (± 70%). There were 25 diagnostic sites for C. tifenestrata, and four diagnostic sites for genus level. One hundred eigthty nine (189) amino acids were alignment, and only one percent of the genes was varied among species. The 107th amino acid (valine) and 138th(threonine) were diagnostics amino acid for C. tifenestrata. Based on nucleotides and amino acids sequences, the phylogeny showed that C. tifenestrata lied on the same nodes with Antheraea, so the Saturniidae family is monophyletic.